Cover Feature: Direct Evidence of the Benzylium and Tropylium Cations as the Two Long‐Lived Isomers of C7H7+ (ChemPhysChem 23/2018). Issue 23 (6th December 2018) - Jusko, Pavol; Simon, Aude; Banhatti, Shreyak; Brünken, Sandra; Joblin, Christine
Abstract : The Cover Feature shows C7 H7 + produced by dissociative ionization of toluene. Combining cryogenic trapping with infrared pre‐dissociation spectroscopy, two structures could be identified: the benzylium and tropylium ions. More information can be found in the Communication by P. Jusko et al. onpage 3182 in Issue 23, 2018 (DOI:10.1002/cphc.201800744 ).